Accuracy of patient-specific implants and additive-manufactured surgical splints in orthognathic surgery — A three-dimensional retrospective study - Rückschloß, Thomas; Ristow, Oliver; Müller, Michael; Kühle, Reinald; Zingler, Sebastian; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Journal of cranio-maxillofacial surgery, 2019)
Introduction - Because of the many limitations of conventional surgery planning for the treatment of orthognathic deformities, as well as advancements in computer-assisted planning, there is an urgent need for technical devices that transfer the surgical plan into the operating theatre. In this regard, additive-manufactured, patient-specific implants (PSI) and additive-manufactured interocclusal splints represent promising approaches. The aim of this retrospective study was to compare the accuracy of these two devices, with regard to preoperative virtual treatment planning for maxillary Le-Fort I advancement surgery using IPS CaseDesigner®, and based on a new analysis method without the use of landmarks. - Materials and methods - A retrospective evaluation of 18 class III patients (n(PSI) = 9; n(splint) = 9), who had undergone virtually planned orthognathic surgery (including maxillary Le Fort I advancement), was performed. The preoperative treatment plan and the postoperative outcome were combined to calculate the translational and rotational discrepancies between the 3D planning and the actual surgical outcome. - Results - For the PSI and splint groups the accuracy of left/right positioning was 0.51 mm ± 0.48 and 1.11 mm ± 1.32 respectively. The accuracy of anterior/posterior positioning was 0.39 mm ± 0.26 and 1.42 mm ± 0.87, and that of up/down-positioning was 0.44 mm ± 0.31 and 0.62 mm ± 0.47. The rotational discrepancies were less than 2° in both groups. Conclusion: The findings demonstrate that both PSI and splint approaches can accurately transfer the virtual planning into the operating theatre. However, PSIs show an overall higher accuracy, especially for anterior/posterior translational movement (p < 0.002).
Gesehen am 17.09.2019